Kami krazie - Kamikrazie; Mat Mega; PonyCanyon Music (Malaysia). (Kuala Lumpur : PonyCanyon Music, 1999)
Contain four rock songs.
CD 1 : Who's Gonna Knock You? / (4:31) -- Who's Gonna Knock You? (The Hardcore mix) / (3:00) -- Infinity Pain / -- We've Got Tha Juice.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music; Songs, Malay